Culture dependent and independent characterization of endophytic bacteria in the seeds of highland barley - Chen, Yulan; Liang, Jinpeng; Zia, Alina; Gao, Xue; Wang, Yong; Zhang, Lingzi; Xiang, Quanju; Zhao, Ke; Yu, Xiumei; Chen, Qiang; Penttinen, Petri; Nyima, Tashi; et al. (Frontiers in Microbiology, 2022)
Endophytes in the seeds of plants have shown plant growth promoting (PGP) properties. We applied culture-dependent and culture-independent methods to study endophytic bacteria in the seeds of Highland barley, an economically important crop and a major part of the local diet in the Tibetan Plateau, China, with potential health benefits. Most of the 86 isolates were assigned into genus Bacillus. Approximately half of the isolates showed PGP properties in vitro, suggesting that the seed endophytes of highland barley are likely to promote the growth since germination. Compared to the not-inoculated plants, inoculation with the isolate B. tequilensis LZ-9 resulted in greater length and number of roots, and in bigger aboveground and root weights. Based on the 16S rRNA gene sequencing, the seed microbiome was majorly affiliated with the phylum Proteobacteria and the family Enterobacteriaceae. Overall, the bacterial community compositions in the different varieties were different from each other. The differences in community compositions were associated with the total and reducing sugar contents and viscosity, thus possibly connected to differences in tolerance against osmotic pressure.